Dye incorporation in polyphosphate gels: synthesis and theoretical calculations - Del Nero,Jordan (2003)
In this work we described theoretical calculations on the electronic structure and optical properties of the dyes crystal violet and malachite green based in semiempirical methods (Parametric Method 3 and Intermediate Neglect of Differential Overlap / Spectroscopic - Configuration Interaction) and the synthesis of a new hybrid material based upon the incorporation of these dyes in an aluminum polyphosphate gel network. The samples are nearly transparent, free-standing thick films. The optical properties of the entrapped dyes are sensitive to chemical changes within the matrix caused either by gel aging or external stimulli such as exposition to acidic and basic vapors that can percolate within the matrix. Our theoretical modeling is in good agreement with the experimental results for the dyes.